Identifying umbrella and indicator species to support multispecies population connectivity in a Himalayan biodiversity hotspot - Penjor, Ugyen; Kaszta, Zaneta M.; Macdonald, David W.; Cushman, Samuel A. (Frontiers in Conservation Science, 2024)
Successful conservation hinges on the reliable prediction and prioritization of population core habitats and dispersal corridors. However, s single-species connectivity has produced mixed results and, in most cases, failed to protect other species under the appealing but often unfulfilled guise of umbrella protection. The objectives of this study were to: (1) identify core habitats and dispersal corridors for population connectivity of 15 terrestrial mammal species across Bhutan, (2) identify indicator species of wildlife connectivity, (3) prioritise core areas and dispersal corridors for the focal umbrella and indicator species, (4) develop composite multispecies connectivity maps and evaluate the effectiveness of the existing protected area network. We identified core habitats and dispersal corridors for each species: resistant kernel density (KD) to identify core habitat areas and factorial least-cost path (LCP) to map dispersal corridors. We used correlation and cluster analyses to identify umbrella and indicator species, and we performed a quantitative ranking to prioritise core areas and corridors for these focal species. Finally, we produced maps of multispecies core areashabitats and corridors, and used it to identifiedy gaps in the existing protected area network (PAN). We found that ungulates were generally more effective than carnivores in serving as umbrella species for core habitat protection, with Asian elephant (Elephas maximus) emerging as the most effective umbrella for core habitats and muntjac (Muntiacus muntjac) for dispersal corridors. We identified six focal connectivity indicator species in Bhutan: tiger (Panthera tigris), dhole (Cuon alpinus), e, clouded leopard (Neofelis nebulosa),, Asiatic black bear(Ursus thibetanus), , Asian elephant, and sambar deer(Rusa unicolor).. Most indicator species' core areas and dispersal corridors outside the protected areas network (the PAN) were in southern Bhutan, indicating opportunities for increased multispecies connectivity through expanding protected area network in this region. A total This is a provisional file, not the final typeset article of 40% of multispecies core areas and 24% of dispersal corridors were under PAN, with large parts of Bhutan offering suitable core areas and corridors for multispecies conservation. Core areas and corridors of the 15 considered species only partially overlapped, stressing the importance of multispecies consideration in designating a wildlife corridors.